Development of a thermal energy storage system with a wide temperature range using a natural mineral mixture as porous support of a phase change material (2021)
ABSTRACT: Among building elements, the envelope is a key component in providing shelter and in regulating the thermal energy of the indoor environment. In this regard, the incorporation of thermal energy storage elements, as phase change materials (PCM), is proposed as a solution to contribute to energy-efficient building performance. Material finishes that incorporate PCMs can minimize the heating and cooling loads through the building envelope due to their high energy storage capacity, achieving thermal comfort inside the building, and increasing thermal inertia. Regarding the type of PCM, fatty acids are an interesting choice because they come from renewable sources, are non-toxic, present no-subcooling and are abundant, which makes them financially competitive with paraffins and salts in the PCM market. Even though, it is recommended to encapsulate them for extend time applications as the solid to liquid phase change can lead to material losses and leakages. Hence, in this work, three binary eutectic mixtures of fatty acids were chosen as potential thermal energy storage materials for being used in building elements. Capric-myristic acid (CA/MA), lauric-myristic acid (LA/MA), and palmitic-stearic acid (PA/SA) mixtures were selected due to their wide range of temperatures that could work for different uses within the construction sector as passive cooling, low temperature solar heating, and domestic water heating. Shape-stabilized PCMs (SS-PCMs) were produced with these eutectics to avoid leakage, using a Colombian natural porous clay as support. The eutectics and SS-PCMs produced were deeply characterized by the authors in terms of thermal properties, thermal stability, thermal reliability (up to 10000 cycles), thermal conductivity, chemical and physical properties, and percentage of leakage, among others. Moreover, within the novelties of this work, the idea that controlling and analyzing the textural properties of the supports used for shape-stabilization of PCMs, from a top-down approach, can optimize the absorption capacity of the PCM and thus, the thermal properties of the general system, was studied. Hence, physical and chemical modifications of the clay support were performed to improve the absorption and thermal properties of the final SS-PCMs. Modifications included heat treatments, granulation, and sylanization of the clay supports. Heat treatments produce more pores into the support that improved leakage retention of the PCM, and sylanization generates covalent bonds between the PCM and the clay. Finally, two configurations for incorporating SS-PCMs in buildings were evaluated using an equipment designed to measure thermal variables in dynamic and steady-state of the materials. The setup aims to simulate indoor and outdoor conditions. First, the three powder SS-PCMs were evaluated in direct contact with the outdoor environment, to analyze their insulation capacities, heat storage, and performance under diurnal cycles. Second, an acrylic-based plaster was designed with the incorporation of two of the SS-PCMs which then was used as a finish of a fiber cement siding. In the last case, the SS-PCM-based acrylic plaster was evaluated as an indoor material, without direct contact with the outdoor environment. The research demonstrated the viability of these samples as potential candidates to be incorporated in building envelopes.